Dampness and mould over 20 years and new onset of respiratory symptoms, asthma and rhinitis - Juan Wang; Mathias Holm; Anna Dahlman-Höglund; Thorarinn Gislason; Hulda Rosa Thorarinsdottir; Christine Cramer; Ane Johannessen; Lars Modig; Rain Jogi; Össur Ingi Emilsson; Andrei Malinovschi; Dan Norbäck; et al. (Journal of Hazardous Materials, 2026)

Exposure to legacy and emerging phthalates and bisphenols in recycling workers: Evidence from the GreenMetalWaste study - Neža Palir; Eva Dock; Malin Engfeldt; Maria Albin; Else Åkerberg Krook; Marie Bengtsson; Anna Dahlman Höglund; Robert Linder; Lars Modig; Christian Lindh; Anja Stajnko; Karin Broberg (Environmental Research, 2026)

Mortality impacts of air pollution and greenness: real-world and counterfactual exposure scenarios in seven Northern European cities - Shanshan Xu; Alessandro Marcon; Randi Jacobsen Bertelsen; Bryndis Benediktsdottir; Jørgen Brandt; Lise Marie Frohn; Camilla Geels; Thorarinn Gislason; Joachim Heinrich; Mathias Holm; Christer Janson; Andrei Malinovschi; et al. (Environmental Research, 2026)

Indoor airborne bacterial communities and adult lung health: A cross-sectional study - Hesham Amin; Christine Cramer; Kai Finster; Francisco Gomez Real; Thorarinn Gislason; Mathias Holm; Christer Janson; Nils Oskar Jögi; Rain Jogi; Andrei Malinovschi; Lars Modig; Dan Norbäck; et al. (International Journal of Hygiene and Environmental Health, 2026)

Metal and dust exposure in workers from the metal recycling industry in Sweden: cross-sectional GreenMetalWaste study - Anja Stajnko; Michael Levi; Malin Engfeldt; Robert Linder; Mats Leeman; Else Åkerberg Krook; Eva Assarsson; Henrik Enquist; Camilla Dahlqvist; Åsa Ek; Karin Lovén; Theo Bodin; et al. (International Journal of Hygiene and Environmental Health, 2026)

Long-term exposure to air pollution and greenness in association with respiratory emergency room visits and hospitalizations: The Life-GAP project - Shanshan Xu; Alessandro Marcon; Randi Jacobsen Bertelsen; Bryndis Benediktsdottir; Jørgen Brandt; Lise Marie Frohn; Camilla Geels; Thorarinn Gislason; Joachim Heinrich; Mathias Holm; Christer Janson; Iana Markevych; et al. (Environmental Research, 2025)

Associations of long-term exposure to air pollution and greenness with incidence of chronic obstructive pulmonary disease in Northern Europe: The Life-GAP project - Shanshan Xu; Alessandro Marcon; Randi Jacobsen Bertelsen; Bryndis Benediktsdottir; Jørgen Brandt; Lise Marie Frohn; Camilla Geels; Thorarinn Gislason; Joachim Heinrich; Mathias Holm; Christer Janson; Iana Markevych; et al. (Environmental Research, 2024)

Hexavalent chromium still a concern in Sweden – Evidence from a cross-sectional study within the SafeChrom project - Zheshun Jiang; Linda Schenk; Eva Assarsson; Maria Albin; Helen Bertilsson; Eva Dock; Jessika Hagberg; Lovisa E. Karlsson; Pete Kines; Annette M. Krais; Stefan Ljunggren; Thomas Lundh; et al. (International Journal of Hygiene and Environmental Health, 2024)

Personal exposure levels to O3, NOx and PM10 and the association to ambient levels in two Swedish cities - Susanna Lohman Haga; Annika Hagenbjörk; Anna-Carin Olin; Bertil Forsberg; Ingrid Liljelind; Hanne Krage Carlsen; Lars Modig (Environmental Monitoring and Assessment, 2021)
Exposure to air pollution is of great concern for public health although studies on the associations between exposure estimates and personal exposure are limited and somewhat inconsistent. The aim of this study was to quantify the associations between personal nitrogen oxides (NO x ), ozone (O 3 ) and particulate matter (PM 10 ) exposure levels and ambient levels, and the impact of climate and time spent outdoors in two cities in Sweden. Subjects ( n = 65) from two Swedish cities participated in the study. The study protocol included personal exposure measurements at three occasions, or waves. Personal exposure measurements were performed for NO x and O 3 for 24 h and PM 10 for 24 h, and the participants kept an activity diary. Stationary monitoring stations provided hourly data of NO x , O 3 and PM, as well as data on air temperature and relative humidity. Data were analysed using mixed linear models with the subject-id as a random effect and stationary exposure and covariates as fixed effects. Personal exposure levels of NO x , O 3 and PM 10 were significantly associated with levels measured at air pollution monitoring stations. The associations persisted after adjusting for temperature, relative humidity, city and wave, but the modelled estimates were slightly attenuated from 2.4% (95% CI 1.8–2.9) to 2.0% (0.97–2.94%) for NO x , from 3.7% (95% CI 3.1–4.4) to 2.1% (95% CI 1.1–2.9%) for O 3 and from 2.6% (95% 0.9–4.2%) to 1.3% (95% CI − 1.5–4.0) for PM 10 . After adding covariates, the degree of explanation offered by the model (coefficient of determination, or R 2 ) did not change for NO x (0.64 to 0.63) but increased from 0.46 to 0.63 for O 3 , and from 0.38 to 0.43 for PM 10 . Personal exposure to NO x , O 3 and PM has moderate to good association with levels measured at urban background sites. The results indicate that stationary measurements are valid as measure of exposure in environmental health risk assessments, especially if they can be refined using activity diaries and meteorological data. Approximately 50–70% of the variation of the personal exposure was explained by the stationary measurement, implying occurrence of misclassification in studies using more crude exposure metrics, potentially leading to underestimates of the effects of exposure to ambient air pollution.